Fetal Deficiency of Lin28 Programs Life‐Long Aberrations in Growth and Glucose Metabolism1. (23rd August 2013) - Shinoda, Gen; Shyh‐Chang, Ng; Soysa, T. Yvanka de; Zhu, Hao; Seligson, Marc T.; Shah, Samar P.; Abo‐Sido, Nora; Yabuuchi, Akiko; Hagan, John P.; Gregory, Richard I.; Asara, John M.; Cantley, Lewis C.; et al.
Abstract: LIN28A/B are RNA binding proteins implicated by genetic association studies in human growth and glucose metabolism. Mice with ectopic over‐expression of Lin28a have shown related phenotypes. Here, we describe the first comprehensive analysis of the physiologic consequences of Lin28a and Lin28b deficiency in knockout (KO) mice. Lin28a/b ‐deficiency led to dwarfism starting at different ages, and compound gene deletions showed a cumulative dosage effect on organismal growth. Conditional gene deletion at specific developmental stages revealed that fetal but neither neonatal nor adult deficiency resulted in growth defects and aberrations in glucose metabolism. Tissue‐specific KO mice implicated skeletal muscle‐deficiency in the abnormal programming of adult growth and metabolism. The effects of Lin28b KO could be rescued by Tsc1 haplo‐insufficiency in skeletal muscles. Our data implicate fetal expression of Lin28a/b in the regulation of life‐long effects on metabolism and growth, and demonstrate that fetal Lin28b acts at least in part via mTORC1 signaling. STEM Cells 2013;31:1563–1573